2014
DOI: 10.1080/02667363.2014.949374
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being and motivation in a Turkish physical education context

Abstract: Using Self Determination as a framework, the purpose of the study was to examine the relationships between basic psychological needs, motivational regulations, self-esteem, subjective vitality, and social physique anxiety in physical education. One thousand and eighty two high school students aged between 14 and 19 [mean (M) = 15.89 ± 0.95 years] from six public high schools participated to the study. Students' basic psychological needs: motivational regulations, subjective vitality and self-esteem served as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
8
0
4
Order By: Relevance
“…An autonomy-related organization of PE increases the intrinsic motivation for doing activities in PE because it is stimulates interest and provides its own reward by satisfying individuals" basic needs for autonomy, competence, and relatedness. The theory has been supported empirically by many PE related studies (Bagøien et al, 2010;Ciyin and Erturan-Ilker, 2014;Erturan-Ilker, 2014;Koka, 2014;Mouratidis et al, 2008;Standage et al, 2012). The interview results of the present study indicate that PE, as it is currently organized, seems to create better conditions for autonomy in high school than in lower secondary school.…”
Section: Development Of Enjoyment In Pe During Lower Secondary Schoolsupporting
confidence: 61%
See 1 more Smart Citation
“…An autonomy-related organization of PE increases the intrinsic motivation for doing activities in PE because it is stimulates interest and provides its own reward by satisfying individuals" basic needs for autonomy, competence, and relatedness. The theory has been supported empirically by many PE related studies (Bagøien et al, 2010;Ciyin and Erturan-Ilker, 2014;Erturan-Ilker, 2014;Koka, 2014;Mouratidis et al, 2008;Standage et al, 2012). The interview results of the present study indicate that PE, as it is currently organized, seems to create better conditions for autonomy in high school than in lower secondary school.…”
Section: Development Of Enjoyment In Pe During Lower Secondary Schoolsupporting
confidence: 61%
“…Several studies point to the selfdetermination theory of Deci and Ryan (2000) as important for creating enjoyment in PE (Bagøien et al, 2010;Ciyin and Erturan-Ilker, 2014;Erturan-Ilker, 2014;Holstad, 2012;Jang et al, 2010;Koka, 2014;Mouratidis et al, 2008;Standage et al, 2012). Deci and Ryan (2000) pointed to three basic needs in all humans: autonomy, relatedness, and competence.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have suggested that this may be due to difficulty in differentiating between external regulation and introjection in children [ 36 ]. As in other child studies [ 30 ], introjection was thus excluded from analysis and external regulation was used as a measure of controlled motivation.…”
Section: Methodsmentioning
confidence: 99%
“…Further, higher levels of controlled motivation have been associated with lower levels of positive affect and lower subjective wellbeing in adults and adolescents [ 27 , 29 ]. While the balance of evidence suggests that controlled motivation may be detrimental to fostering positive mental health, not all studies have reported a negative relationship between controlled motivation and mental health [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Τα αποτελέσματα της μελέτης έδειξαν ότι το παρεχόμενο, από τον εκπαιδευτικό ΦΑ, ενδυναμωτικό κλίμα σχετίστηκε θετικά με την ικανοποίηση των ΒΨΑ και αρνητικά με την ματαίωση των ΒΨΑ, επαληθεύοντας την 1 η ερευνητική υπόθεση. Τα ευρήματα επιβεβαίωσαν μελέτες που επισήμαναν ότι η εκπλήρωση των ΒΨΑ σχετίστηκε θετικά τόσο με ένα κλίμα προσανατολισμένο στη μάθηση όσο και με ένα κλίμα υποστήριξης της αυτονομίας και της αυτοκαθοριζόμενης παρακίνησης (Bartholomew, et al, 2018;Erturan-Ilker, 2014;Koka & Hagger, 2010;Ntoumanis, 2005;Ommundsen, 2006;Pérez-González, et al, 2019;Standage & Gillison, 2007). Εν αντιθέσει, εντοπίστηκε ότι το αποδυναμωτικό κλίμα σχετίστηκε θετικά με την ματαίωση των ΒΨΑ, πιστοποιώντας, εν μέρει, την 2 η ερευνητική υπόθεση και επικυρώνοντας πορίσματα προηγούμενων μελετών, όπου ένα κλίμα με έμφαση στο εγώ και στην ελεγχόμενη συμπεριφορά παρεμπόδιζε την ικανοποίηση των ΒΨΑ (Álvarez et al, 2012;Balaguer et al, 2012;Haerens, et al, 2018 (Wang & Biddle, 2001), καθίσταται αναγκαίο μελλοντικά να επανεξεταστεί ενδελεχώς η σχέση ικανοποίησης των ΒΨΑ και του αποδυναμωτικού κλίματος.…”
Section: συζητησηunclassified